1991
DOI: 10.1152/ajprenal.1991.261.5.f767
|View full text |Cite
|
Sign up to set email alerts
|

Chronic K depletion stimulates rat renal brush-border membrane Na-citrate cotransporter

Abstract: Chronic K depletion (KD) causes hypocitraturia. In the present studies, the effect of KD, induced by a low-K diet for 14 days (serum [K] 4.1 +- 0.1, control vs. 2.2 +/- 0.1 meq/l, KD, P less than 0.01), on renal cortical brush-border membrane (BBM) Na-citrate cotransporter activity was examined. KD significantly decreased fractional citrate excretion (3.90 +/- 0.68 vs. 0.53 +/- 0.10%, P less than 0.01). This was paralleled by a significant increase in the initial linear rate of BBM Na-dependent citrate transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 0 publications
1
56
0
Order By: Relevance
“…Citrate is freely filtered in the glomerulus, and its reabsorption in the proximal tubule is the major determinant of the rate of renal excretion. Proximal citrate reabsorption is an active transport and mediated by an apical Na-citrate cotransporter, which carries three Na + with one citrate 2-, and is thus electrogenic 17) in nature. In this study, we exposed rat renal brush border membrane vesicles (BBMV) to CoCl 2 and NiCl 2 , respectively, and comparatively investigated the direct effect of these exposure on citrate uptake by BBMV to elucidate the renal toxic mechanisms of Co and Ni.…”
Section: Introductionmentioning
confidence: 99%
“…Citrate is freely filtered in the glomerulus, and its reabsorption in the proximal tubule is the major determinant of the rate of renal excretion. Proximal citrate reabsorption is an active transport and mediated by an apical Na-citrate cotransporter, which carries three Na + with one citrate 2-, and is thus electrogenic 17) in nature. In this study, we exposed rat renal brush border membrane vesicles (BBMV) to CoCl 2 and NiCl 2 , respectively, and comparatively investigated the direct effect of these exposure on citrate uptake by BBMV to elucidate the renal toxic mechanisms of Co and Ni.…”
Section: Introductionmentioning
confidence: 99%
“…Citrate is freely filtered at the glomerulus, and its reabsorption in the proximal tubule is the major determinant of the rate of renal excretion 5) . In our previous studies 6, 7) , we reported that the preincubation of rat renal brush border membrane vesicles (BBMV) with 5 mM cisplatin for 4 and 8 hours and 100 mM carboplatin, a second-generation platinum coordination complex, for 8 hours significantly inhibited the citrate uptake compared with that of the control BBMV.…”
Section: Introductionmentioning
confidence: 99%
“…Citrate is freely filtered at the glomerulus, and its absorption by the transporters in the proximal tubule is the major determinant of rate 7) . In the present study, we exposed rat renal brush border membrane vesicles (BBMV) to vanadium pentoxide (V 2 O 5 ) and investigated the direct effect of vanadium exposure on the citrate uptake of the BBMV.…”
mentioning
confidence: 99%